Intimate Partner Violence: A Multinational Test of Cultural Spillover Theory - Lysova, Alexandra (Journal of interpersonal violence, 2021)
Cultural spillover theory asserts that the prevalence of socially legitimate violence to attain ends for which there is widespread social approval is part of the explanation for the prevalence of illegitimate violence. This study was a test of the cultural spillover theory as it applies to intimate partner violence (IPV). Based on data from the International Dating Violence Study (IDVS) in 32 countries, we tested the proposition that agreement with socially approved forms of violence “spills over” into violence against an intimate partner. Two versions of an index to measure legitimate violence were constructed: (a) An individual-level legitimate violence index based on the beliefs and behavior of 14,252 university students in 32 nations in the IDVS and (b) a nation-level legitimate violence index consisting of the mean of the student scores on the legitimate violence index for each of the 32 nations in the IDVS. We used the revised Conflict Tactics Scales to obtain the data on physical violence and injuries inflicted by the students in the IDVS. Analysis of covariance (ANCOVA) was used to test the hypothesized relation of the individual student legitimate violence index to IPV. Socioeconomic status, limited disclosure scale, respondent’s age, and length of the relationships were included as covariates. Multiple regression analyses were conducted to further investigate the associations between legitimate violence index obtained from the aggregated student data and the nation-level IPV, controlling for the gross domestic product (GDP) index and limited disclosure scale. Both individual- and nation-level analyses consistently supported cultural spillover theory’s explanation of IPV. The association between legitimate violence and IPV at both levels of analysis was stronger for women than men, which is consistent with some previous studies. The results suggest that reducing legitimate violence can make an important contribution to reducing IPV.